(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article discusses the features of prescription writing in medicine. It contains information about the division of prescription writing into nine parts, the use of Latin terms, the expression of drug forms, the use of doses and amounts, and the abbreviations of prescriptions.